Ute och cyklar? - Kristensson, Ingrid (2009)

(untitled)
Well-functioning bicycle paths are relevant issues in today´s society as a way to increase active transport. Active transport means working for a better global climate, urban environment and public health. What we experience on a bicycle affects the choice of a bicycle path and is a subject where there is much left to explore. This essay examines methods in environmental psychology literature that measure the experiences of landscape. The aim is to find and apply methods to measure the experience of two bicycle paths in the Skåne plains. The experience was measured in two different ways, by asking commuters on the path and by a preference study were pictures of the paths were judged by inhabitants in the neighboring town of Lund. The aim was to find good and bad qualities of the two paths, as well as to evaluate whether the methods are appropriate to measure the experience of cycle paths. Photos of tunnels under roads, only containing grass slopes and road environment, were low in preference, while images with a lot and varied vegetation were high in preference. Spontaneous comments from commuters were that the traffic and the wind are disturbing elements on the roads, while the variety and feeling of history are positive factors. The two methods complemented each other, as the photos show examples of good and poor environments, while the survey provides answers to the feeling as a hole. The need for continued research is necessary and the subject is exciting to explore.